Viable biobanking of primary head and neck squamous cell carcinoma123. (8th January 2013) - Godoy, Jose M.; Sewell, Andrew; Johnston, Benjamin; Brown, Brandee T.; Lu, Xinyuan; Sinard, Robert J.; Rohde, Sarah; Mannion, Kyle; Netterville, James L.; Yarbrough, Wendell G.
Abstract Objectives/Hypothesis: To determine the feasibility of viable storage of head and neck squamous cell carcinoma (HNSCC) for regrowth of cells in culture. Study Design: Laboratory‐based translational study. Methods: Methods for intermediate‐term frozen storage of viable HNSCC were explored using small pieces of primary tumor and dissociated HNSCC cells after short‐term culture. Viable cells after freezing were confirmed by adherence to tissue culture plates, cell morphology, and increased cell or colony density. Two cultures were immunostained for cytokeratin to confirm epithelial origin of viable cultured cells after freezing. Results: Six primary HNSCCs (two oral cavity, three larynx, one oropharynx) and two HNSCCs that had been passaged through a xenograft (two oral cavity) were dissociated to single cells and grown in short‐term cell culture for 0 to 12 passages. After short‐term culture, cells were frozen for up to 8 months, thawed, and replated. Frozen cells derived from all tumors (six primary and two xenografts) were successfully replated with cultures lasting >7 days with seven of eight tumors presenting increased colony or cell density over 1 week of growth after freezing. In total, 15 of 15 tested samples derived from six primary and two xenografted HNSCCs were viable after freezing. Conclusions: In the current study, we show that biopreservation of primary or xenografted HNSCC using short‐term cell culture is feasible. Initial short‐term cell culture was required for successful storage and viability of frozen cells. These proof‐of‐principle studies, if more widely implemented, could improve preclinical testing of new therapies for HNSCC. Laryngoscope, 2013